Access to justice and effective remedy: Constitution and administrative law - Aróstica Maldonado, Iván (Derecho Público Iberoamericano, 2017)
This work consists of an historical analysis regarding the prospect that the individuals have had and currently have in accessing to justice and obtaining effective remedies in Chile when confronted in a dispute of legal importance against the government, specially the Administration. It concludes with a diagnostic of the status quo. This allows to understand, from this special standpoint, the way in which in our country the Rule of Law has been enshrined.